Analisis Kelayakan Usahatani Padi Petani Urban di kelurahan Bangkala Kecamatan Manggala - Molla, Saleh; Nurdin, Nurdin (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
Every business that carried out is expected to be sustainable. Businesses in the agricultural sector can continue if they can provide benefits to the management. The sustainability of a business in the agricultural sector can be seen in social economics and ecological sustainability. Economic sustainability can be seen in terms of economic feasibility, for example, being able to generate profit or income. While social sustainability is indicated by the existence of cooperation and the ability to minimize completeness among stakeholders, especially among fellow farming actors, while an Ecological sustainability farming business occurs when there is an effort among farming actors to conserve land and apply organic farming. This study aims to determine the feasibility of urban rice farming in Bangkala Village, Manggala District, Makassar City. Respondentd were chosen purposively sampling technique. While the data was analyzed by using B/C ratio. The results of the analysis of the B/C ratio obtained were 0.72, meaning that rice farming for urban farmers in the Bangkala sub-district, Manggala District, from an economic point of view, was no longer feasible or not longer profitable. Therefore farmers have to look for other sources of income such as becoming construction workers, sellers, or starting a business, so the government needs to intervene to provide training to build the skills needed by farmers.